2003
DOI: 10.1177/002215540305100309
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Giant Protein AHNAK (Desmoyokin) in Muscle and Lining Epithelial Cells

Abstract: S U M M A R YHere we report a detailed analysis of the expression and localization of the giant protein AHNAK in adult mouse tissues. We show that AHNAK is widely expressed in muscle cells, including cardiomyocytes, smooth muscle cells, skeletal muscle, myoepithelium, and myofibroblasts. AHNAK is also specifically expressed in epithelial cells of most lining epithelium, but is absent in epithelium with more specialized secretory or absorptive functions. In all adult tissues, the main localization of AHNAK is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 28 publications
(43 reference statements)
4
54
0
3
Order By: Relevance
“…Although the AHNAK protein was originally identified as a nuclear protein, several lines of evidence suggest that the protein is localized in the plasma membrane (3,(31)(32)(33). Gentil et al (31) reported that the main localization of AHNAK is at the plasma membrane in adult muscle cells and the lining of the epithelium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the AHNAK protein was originally identified as a nuclear protein, several lines of evidence suggest that the protein is localized in the plasma membrane (3,(31)(32)(33). Gentil et al (31) reported that the main localization of AHNAK is at the plasma membrane in adult muscle cells and the lining of the epithelium .…”
Section: Discussionmentioning
confidence: 99%
“…Gentil et al (31) reported that the main localization of AHNAK is at the plasma membrane in adult muscle cells and the lining of the epithelium . Hashimoto et al (3) reported the PMA-induced translocation of whole AHNAK protein to plasma membrane in FIG.…”
Section: Discussionmentioning
confidence: 99%
“…15,52 In both intact and injured spinal cord, AHNAK-IR is found within blood vessels that are also positive for either SMI 71 …”
Section: Intrathecal Chabc Injections Induce Cspg Degradation At the mentioning
confidence: 99%
“…It is highly expressed in muscle as well as in epithelial and endothelial cell layers with barrier function [4,5,6,7]. First described as desmoyokin in bovine epithelia [8], it was later identified as a tumor-related protein with nuclear localization in cancer cell lines [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As a component of the L-type Ca 2+ channel complex, Ahnak1 participates in Ca 2+ handling in T cells [24], cardiomyocytes [23], and osteoblasts [25]. Several reports describe a role for Ahnak1 in the cells of the vascular bed [4,7,26,27,28,29]. They describe a distinct Ahnak1 expression in barrier-forming endothelial cells in the blood-brain barrier [7], and indicate a role in lysosome fusion and membrane repair in endothelial cells in vitro [26].…”
Section: Introductionmentioning
confidence: 99%